Effectiveness of Soursop Leaf Extract in Reducing Glucose Levels in Diabetes Mellitus Patients: Literature Study - Elisa Issusilaningtyas; Nikmah Nuur Rochmah (Pt. Anagata Sembagi Education, 2024)
Alternative treatment for lowering sugar levels can be done through the use of herbal plants such as soursop leaves. This study aims to evaluate the effectiveness of soursop leaf extract (Annona muricata L.) in reducing blood glucose levels in Diabetes Mellitus (DM) patients. This research uses a literature study method, with data taken from scientific articles or journals within the last five years. Data was collected using the Google Scholar search engine with the keywords